2015
DOI: 10.3941/jrcr.v9i3.2037
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Hoffa's fat pad impingement secondary to a thickened infrapatellar plica: a case report and review of the literature

Abstract: We report a case of posterior hoffitis in a middle-aged woman with no prior history of significant major trauma. Her symptoms of anterior knee pain and limited extension failed conservative measures. Preoperative magnetic resonance imaging demonstrated a significantly thickened infrapatellar plica tethering Hoffa's fat pad in the anterior interval of the knee. Arthroscopic resection of the infrapatellar plica resulted in complete resolution of symptoms within six months following the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although most studies reported restricted range of motion and pain at the end of extension, one study reported painful limitation at 20 degrees flexion. 21 Hoffa's test was positive in seven patients. 13,15,16,[18][19][20]22 Retrospective studies described pain and tenderness around the patella and painful terminal extension.…”
Section: Clinical Presentationmentioning
confidence: 91%
See 2 more Smart Citations
“…Although most studies reported restricted range of motion and pain at the end of extension, one study reported painful limitation at 20 degrees flexion. 21 Hoffa's test was positive in seven patients. 13,15,16,[18][19][20]22 Retrospective studies described pain and tenderness around the patella and painful terminal extension.…”
Section: Clinical Presentationmentioning
confidence: 91%
“…The duration was in weeks in 5 of 14 patients in case reports, [13][14][15][16] from weeks to months in 2 of 14 patients 16,17 and years in 7 of 14 patients. 16,[18][19][20][21][22] Six of the 14 patients had worsening of the pain with activity. [13][14][15][16]21,22 A total of six patients described a history of trauma that predated this condition: hyperflexion in two patients 15,19 as well as chronic repetition in four patients.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation